x^3+y^3

Factorization of x3 + y3

It can be seen in most book that x3 + y3 can be factorized by dividing the expression by  (x + y).  After division we get a quotient of  (x2 - xy + y2) with no remainder.  Therefore

Bạn đang xem: x^3+y^3

However, this method involves knowing the factor (x + y) beforehand (and the understanding of Factor Theorem). This article giao dịch with different methods of handling this factorization.

(Method 1) (Binomial theorem)

=

Move the last two terms to tướng the other side, we get:

=

(Method 2)

Move the last two terms to tướng the other side

=

(Method 3) (add a term and subtract the same term)

=

Xem thêm: một bóng đèn có khối lượng 500g

=

=

=

(Method 4)

Can you continue with the factorization by grouping method?

(Method 5)      (change variable)

Consider  y = u V x   (1)

=

=,      by (1), u = x + y

=

=

M        Replacing hắn by (-y), you can get a new identity :

Xem thêm: soạn ngữ văn 10 cánh diều

(Exercise)    Prove

by following the methods above. Be careful to tướng note the sign of the identity.